Economic and Environmental Approaches to Developing a System of Integrated Water Resources Management in the Kuyalnik Estuary Basin - SERBOV, Mykolai G. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The purpose of this research is to investigate the economic and environmental approaches to developing a system of integrated water resources management in the Kuyalnik Estuary basin. Methodological economic and environmental approaches were used to create a system of integrated water resources management in the basin of the Sukhyi Estuary and to evaluate the individual components of the water balance. The research used the ecosystem approach, which was based on the notion that ‘nature is an equal partner’. Water resources management took into consideration their significant transformation under the effect of water management, as well as short-term reports regarding the hydro-meteorological characteristics of the Kuyalnik Estuary. The results show that the development of a system of integrated water resources management should be based on the general calculation of all the components of natural and artificial water restorers, which enables balancing water resources and developing a rational system of management.
Keywords: water resources, integrated management, Kuyalnik Estuary, Black Sea region, water as a commodity